Diagnostic contribution of cytological specimens obtained from biopsies during gastrointestinal endoscopy in dogs and cats. (9th November 2016) - Ruiz, G.; Verrot, L.; Laloy, E.; Benchekroun, G.
Abstract : Objectives: The aims of this study were to compare cytological samples obtained from endoscopic biopsies using "imprint" and "squash" techniques, and to evaluate the potential value of cytology compared to histology in reaching the diagnosis. Materials and Methods: Eighteen dogs and five cats undergoing endoscopy for chronic gastrointestinal signs were prospectively included. Imprint and squash samples were obtained from one biopsy and then analysed. Comparison between cytology and histology was performed using Cohen's j coefficient. Results: Appropriate samples for cytological evaluation were more often obtained with the squash technique (96% of the cases versus 68% with the imprint technique). The diagnoses obtained with cytological samples and by histology, considered as the gold standard, were compared. The same diagnosis was obtained with the squash technique in 65% of the cases. Furthermore, cytology was considered complementary to histology for gastric spiral organisms and mast cells identification. Clinical Significance: These results suggest that squash cytology obtained from endoscopic biopsies of the gastrointestinal tract can provide relevant and additional information to histology in dogs and cats.